Intergenerational Leadership - PARSEHYAN, BESTE GÖKÇE (My University, 2019)
From Machiavelli up until today, leadership has been a topic researched by many social scientists. While leadership research has found scientific basis towards the end of the 20th century, today, there are still many theoretical evaluations undertaken. There is a lot of rhetoric regarding leadership; how to become a successful leader, what is effective leadership, what is the truth about leadership, unsuccessful leadership examples etc. These are written about in line with the experiences we encounter and experience in our daily work environment. The main problem today can be said to be as follows: How can leaders sustain long term success if followers are short term and moving through a revolving door? There are members of five different generations in ourworking environments: veteran generation (1925-1946), baby boom generation (1946-1960), generation X (1960-1980), generation Y (1980-1995) and generation Z (1995-2010). By working together, these different generations provide leadership to one another. As the veteran generation and baby boomers are slowly going into retirement, they are leaving their duties to generations X, Y and Z. At this point, generation Alpha will become part of the cycle. There have been four different scenarios developed regarding the type of leadership that will be in place in 2050 when the generation Alpha will become leaders: BioCircuity Leadership, High-pod Leadership, Automaton Leadership, and Murmeration Leadership. These four different scenarios have been designed according to the communication between generations and will be in place in 2050. However, at the moment, it is impossible to tell which scenario will dominate.
Keywords: Intergenerational Leadership; Generation X; Generation Y; Generation Z; Generation Alpha